BEHAVIOR OF THE EMERGENCE OF NATIVE FOREST SEEDLINGS FOR THE PURPOSE OF RECOVERY OF THE RIPARIAN FOREST - Jesus, Janisson Batista de; Ferreira, Robério Anastácio; Gama, Dráuzio Correia (Floresta, 2018)
Understanding the behavior of the emergence of native forest seeds is essential to achieve greater successes in forest recovery. Therefore, this study aimed to evaluate the emergence of native forest species (Cassia grandis L.F., Cecropia pachystachya Trec., Enterolobium contortisiliquum (Vell.) Morong, Guazuma ulmifolia Lam., and Libidibia ferrea var. leiostachya (Benth.) L.P.Queiroz.) in riparian areas of the Piauitinga River, in the municipality of Lagarto (state of Sergipe, Brazil). The experiment was carried out in a randomized block design (DBC) with four blocks in triple scheme (4 x 2 x 6): four forest species emerged (Cassia grandis, Enterolobium contortisiliquum, Guazuma ulmifolia, Libidibia ferrea var. leiostachya), with and without treatment to overcome dormancy, evaluated every fortnight for 90 days (6 periods). It was verified by the statistical analysis that the four species that had emergencies interacted in the two treatments used throughout the six evaluation periods. The species, in both treatments, presented a large number of seeds emerged in the first weeks after sowing, reducing over time. The species studied have a characteristic pattern of emergence over time, considering both seeds with and without treatment to overcome dormancy.